Sobre Berenguer Mercader, anfitrión del Parlament de Joan Roís de Corella, y demás contertulios. - RUBIO VELA, AGUSTÍN (Scripta, 2019)
Documentary research about the fellow participants in the Parlament en casa de Berenguer Mercader, by Joan Roís de Corella: Berenguer Mercader, Joan Escrivà, Guillem Ramon de Vilarrasa, Lluís de Castellví and don Joan de Pròxita; and critical analysis of the arguments put forward to question the identity of the batle general as actual host of the meeting.